135 Effect of Gossypol from Cottonseed Meal on Growth Performance, Plasma Gossypol, and Complete Blood Cell Counts in Commercial Growing Pigs: A Preliminary Study on Feral Hog Control. (7th May 2021) - Mudarra, Richard A; Tsai, Tsung Cheng Cheng; Hansen, Christopher; Littlejohn, Brittni P; Maxwell, Charles V; Rorie, Rick
Abstract: To evaluate the effect of cottonseed meal (CSM) on growth performance, plasma gossypol and complete blood cell (CBC) counts in growing pigs, 40 gilts (Exp 1) and 24 boars (Exp 2), 63 day of age (19.85±0.43 kg), were randomly allotted to 1 of 4 and 3 treatments with 2 replicates/treatments, respectively. Treatments for Exp 1 during phase 1–3 (14 d/phase) were a nutrient adequate control diet (NRC, 2012) without CSM (0% gossypol), and increasing levels of CSM was added to produce diets containing 0.01%, 0.02% and 0.04% gossypol to form treatments 2 to 4, respectively. For Exp 2, treatments were the same as those in the gilt trail, except 0.01% gossypol treatment was eliminated. All pigs were fed a common diet without CSM in phase 4 (14 d). Whole blood was obtained from two close-to-average pen-BW pigs repeatedly at each phase to determine CBC in Exp 1 and plasma gossypol in Exp 1 and 2. Data were analyzed using the Mixed procedures of SAS (Cary, NC). ADG did not significantly differ between treatments in phase 1&2 (P > 0.05). In phase 3, ADG decreased linearly and quadratic (P < 0.05) with increasing level of CSM in gilts and boars, respectively, while ADFI did not differ. Neutrophil concentration was higher while mean corpuscular volume (MCV) was lower in gilts fed CSM on d 42 than those fed control regardless level of inclusion, whereas after 14 d of CSM withdrawal, neutrophil level was similar to control and MCV remained low (Treatment*day, P < 0.01). Plasma gossypol increased with increasing level of CSM in both gilts and boars during phase 1–3, and was still higher than control after pigs were fed a common diet for 14 d (P < 0.05). In conclusion, cottonseed meal derived gossypol impairs growth performance, and increase plasma gossypol in gilts and boars.